Sigma receptors : their role in disease and as therapeutic targets - Smith, Sylvia B.; Su, Tsung-Ping (Springer, 2017)
"Originally confused with opioid receptors and then orphan receptors with no biological function, Sigma Receptors are now recognized as relevant to many degenerative diseases with remarkable potential as therapeutic targets. In this text, new information about the structure of sigma 1 receptor, its binding sites are provided as well as its expression in many cell types. It's putative role in degenerative neuronal diseases including amyotrophic lateral sclerosis, Alzheimer's disease, Parkinson's disease, Huntington's disease, pain, drug addiction and locomotor activity. Their roles in possible treatments for blinding retinal diseases emphasize the tremendous far-reaching potential for ligands for these receptors. Exciting breakthroughs in this dynamic field in the last decade are reported herein, which will guide future investigators in determining the full potential of this unique, yet abundantly expressed protein"--Publisher's description.
Keywords: Nervous system -- Degeneration.; Sigma receptors.; elektronické knihy; electronic books